Expression of Mas-related gene X2 on mast cells is upregulated in the skin of patients with severe chronic urticaria - Fujisawa, Daisuke; Kashiwakura, Jun-ichi; Kita, Hirohito; Kikukawa, Yusuke; Fujitani, Yasushi; Sasaki-Sakamoto, Tomomi; Kuroda, Kazumichi; Nunomura, Satoshi; Hayama, Koremasa; Terui, Tadashi; Ra, Chisei; Okayama, Yoshimichi (Journal of allergy and clinical immunology, 2014)
Wheal reactions to intradermally injected neuropeptides, such as substance P (SP) and vasoactive intestinal peptide, are significantly larger and longer lasting in patients with chronic urticaria (CU) than in nonatopic control (NC) subjects. Mas-related gene X2 (MrgX2) has been identified as a receptor for basic neuropeptides, such as SP and vasoactive intestinal peptide. Mast cell (MC) responsiveness to eosinophil mediators contributes to the late-phase reaction of allergy. We sought to compare the frequency of MrgX2 expression in skin MCs from patients with CU and NC subjects and to identify the receptor for basic eosinophil granule proteins on human skin MCs. MrgX2 expression was investigated by using immunofluorescence in skin tissues from NC subjects and patients with severe CU and on skin-derived cultured MCs. MrgX2 expression in human MCs was reduced by using a lentiviral small hairpin RNA silencing technique. Ca2+ influx was measured in CHO cells transfected with MrgX2 in response to eosinophil granule proteins. Histamine and prostaglandin D2 levels were measured by using enzyme immunoassays. The number of MrgX2+ skin MCs and the percentage of MrgX2+ MCs in all MCs in patients with CU were significantly greater than those in NC subjects. Eosinophil infiltration in urticarial lesions was observed in 7 of 9 patients with CU. SP, major basic protein, and eosinophil peroxidase, but not eosinophil-derived neurotoxin, induced histamine release from human skin MCs through MrgX2. MrgX2 might be a new target molecule for the treatment of wheal reactions in patients with severe CU.